Implementation of the basic education assistance module (BEAM) programme: the case of Zaka North District in Masvingo) Province. - Mangwaya, Ezron (2016)
Poor and vulnerable learners are on the increase in developing countries. This has been result of among other factors, low gross domestic product, economic down turn, and the emergence and spread of the HIV/AIDS pandemic. The latter has resulted in child headed families which can barely fend for their needs. This study investigates how an intervention programme called Basic Education Assistance programme has been implemented in the Zaka North district of Masvingo province in Zimbabwe. The programme was meant to ensure that poor and vulnerable primary school learners benefit with respect to tuition fees, school levies and examination fees. A descriptive survey was used in the study. Findings indicate that not all students identified as needy end up getting assistance. This is due to insufficient resources as well as factors related to the composition of the selection committee. The study proposes interventions which could be used to enhance transparency and an equitable distribution of available resources.